HLA‐DRB1 Typing by Micro‐Bead Array Assay Identifies the Origin of Early Lymphoproliferative Disorder in a Heart Transplant Recipient. Issue 3 (17th January 2013) - Fedrigo, M.; Poli, F.; Esposito, G.; Feltrin, G.; Toscano, G.; d'Agostino, C.; Schiavon, B.; Gerosa, G.; Amadori, A.; Valente, M.; Thiene, G.; Angelini, A.
<x xml:space="preserve">Abstract</x> We report the case of a 68‐year‐old woman who underwent heart transplantation for hypertrophic cardiomyopathy. Two months after the transplant she developed mild fever and dyspnea with a marked drop in left ventricle ejection fraction of 31%. Coronary angiography was negative for cardiac allograft vasculopathy. Endomyocardial biopsy revealed ischemic damage with no evidence of acute cellular rejection, antibody‐mediated rejection or viral myocarditis. A neoplastic process was suspected even though full‐body computerized tomography was negative for malignancy. The patient died 4 months after transplantation. The autopsy showed acute antero‐septal myocardial infarction due to a nodular epicardial EBV‐related posttransplant lymphoproliferative disorder (PTLD) infiltrating the left anterior descending coronary artery with occlusive neoplastic thrombosis. We highlight two major aspects of this case: (1) the unusual occurrence of early PTLD involving the cardiac allograft and causing a fatal outcome, (2) the application of an immunological technique for HLA‐DRB1 typing to posttransplant paraffin‐embedded autopsy material to identify the recipient origin of this early malignancy, thus excluding a possible donor‐transmitted neoplasm.